2001
DOI: 10.1111/1467-6451.00161
|View full text |Cite
|
Sign up to set email alerts
|

Prices and Price Dispersion on the Web: Evidence from the Online Book Industry

Abstract: Using data collected between August, 1999, and January, 2000, covering 399 books, we examine pricing by thirty‐two online United States‐based bookstores. At the aggregate level, we find that both advertising and competitive structure had the predicted effects. More competition led to lower prices and to lower price dispersion. Holding competitive structure constant, more widely advertised items also had lower prices. At the firm level, we observe considerable heterogeneity in behavior. Firms had differentiated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 272 publications
(76 citation statements)
references
References 8 publications
3
72
1
Order By: Relevance
“…In contrast, many other studies have found that online retailers tend to charge lower prices than traditional retailers (e.g., Brynjolffson & Smith, 2000;Chevalier & Goolsbee, 2003;Clay, Krishnan, & Wolff, 2001;Clemons, Hann, & Hitt, 2002;Smith & Brynjolfsson, 2001). For example, Brynjolfsson and Smith (2000) compared prices of books and CDs sold through the Internet and through conventional channels.…”
Section: Price Levels In the Internet Marketsmentioning
confidence: 96%
See 4 more Smart Citations
“…In contrast, many other studies have found that online retailers tend to charge lower prices than traditional retailers (e.g., Brynjolffson & Smith, 2000;Chevalier & Goolsbee, 2003;Clay, Krishnan, & Wolff, 2001;Clemons, Hann, & Hitt, 2002;Smith & Brynjolfsson, 2001). For example, Brynjolfsson and Smith (2000) compared prices of books and CDs sold through the Internet and through conventional channels.…”
Section: Price Levels In the Internet Marketsmentioning
confidence: 96%
“…For example, Bailey (1998) found that online prices for books, CDs, and computer software were higher than those in conventional stores. Clay, Krishnan, and Wolff (2001) and Clay, Krishnan, Wolff, and Fernandes (2002) compared prices between online and physical stores and found that average prices were similar in both online and offline book markets. But taking sales tax and shipping cost into account, total prices were lower in conventional stores than in online stores.…”
Section: Price Levels In the Internet Marketsmentioning
confidence: 99%
See 3 more Smart Citations